PEMBUATAN ARANG AKTIF KAYU KARET UNTUK NAHAN PEMURNI MINYAK DAUN CENGKEH - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
EzperlmentaUtudy on ltmna •activation of rubber wood charcoal (Hewa bnalllMn•) to prodw activated claarooal.• reported in tlu. paper. The PurPo• of tlu. ,...,.ch la to dudy the of tempeniture and reaction time on the activa te<I charcoal yield and quality. . De octlvated eharcoal jlroduced from flail uperiment N utm.ed to re'/lnllthe crude oa from elo• ,_, oa. TflS fr*ltmlmt tem,,.,ature for actlva